2016
DOI: 10.1016/j.ultrasmedbio.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Clinically Significant Prostate Cancers using 3-D In Vivo Acoustic Radiation Force Impulse Imaging with Whole-Mount Histology Validation

Abstract: Overly aggressive prostate cancer (PCa) treatment adversely affects patients and places an unnecessary burden on our health care system. The inability to identify and grade clinically significant PCa lesions is a factor contributing to excessively aggressive PCa treatment, such as radical prostatectomy, instead of more focal, prostate-sparing procedures such as cryotherapy and high-dose radiation therapy. We have performed 3-D in vivo B-mode and acoustic radiation force impulse (ARFI) imaging using a mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Other investigators have reported several factors of increase in prostate elastic modulus with cancer (i.e., in PZ a factor of 3.2 (Krouskop et al , 1998), 2.6 (Zhang et al , 2008) (mechanical stress testing at 150 Hz), and in (Dresner et al , 2003) (mechanical frequency of 350 Hz) tumor was approximately twice as stiff as healthy prostate. Recently, acoustic radiation force imaging (ARFI) has been explored in combination with B-mode ultrasound imaging to map prostate anatomical zones (Palmeri et al , 2015), and to identify prostate cancer lesions in vivo with retrospective evaluation from whole specimen prostatectomy histopathology (Palmeri et al , 2016) (4.6–5.4 MHz). ARFI in combination with B-mode ultrasound was found to compare well with T 2 w MRI for mapping prostate anatomy, and was highly accurate in mapping prostate cancer, i.e., 71.4% of lesions were identified in ARFI.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported several factors of increase in prostate elastic modulus with cancer (i.e., in PZ a factor of 3.2 (Krouskop et al , 1998), 2.6 (Zhang et al , 2008) (mechanical stress testing at 150 Hz), and in (Dresner et al , 2003) (mechanical frequency of 350 Hz) tumor was approximately twice as stiff as healthy prostate. Recently, acoustic radiation force imaging (ARFI) has been explored in combination with B-mode ultrasound imaging to map prostate anatomical zones (Palmeri et al , 2015), and to identify prostate cancer lesions in vivo with retrospective evaluation from whole specimen prostatectomy histopathology (Palmeri et al , 2016) (4.6–5.4 MHz). ARFI in combination with B-mode ultrasound was found to compare well with T 2 w MRI for mapping prostate anatomy, and was highly accurate in mapping prostate cancer, i.e., 71.4% of lesions were identified in ARFI.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound has been shown to augment breast cancer diagnosis by mammography, particularly for women with dense breast tissue [2] [5] , and evidence continues to grow for the use of ultrasound as a primary modality of breast cancer diagnosis in resource-limited settings, including the use of ultrasound-guided fine needle aspiration [6] [8] . Ultrasound is also used to guide targeted biopsies for prostate cancer diagnosis as well, lowering cost and overtreatment [9] . Additionally, as the development of promising, low-cost contrast agents for image-guided therapeutics continues, ultrasound has the potential to play a role in targeted treatment and disease monitoring [10] .…”
Section: Imaging Technologies For the Detection And Diagnosis Of Cancmentioning
confidence: 99%
“…2.3 Correlations between cervical smooth-muscle force generation and acoustic backscatter-coefficient parameters, Andrew P. Santoso 1 , Joy Vink 2 , George Gallos 3 , Helen Feltovich 1,4 , and Timothy J. Hall 1 , 1 Medical Physics, University of Wisconsin-Madison, Madison, WI; 2 Department of Obstetrics and Gynecology, Columbia University Medical Center, New York, NY; 3 Department of Anesthesia, Columbia University Medical Center, New York, NY; and 4 Maternal Fetal Medicine, Intermountain Healthcare, Provo, UT, apsantoso@wisc.edu Objectives: Smooth muscle cells in the human cervix may play a significant role in cervical function during pregnancy. (1) To date, noninvasive methods to evaluate cervical smooth muscle cell activity are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Identified regions of suspicion in the in vivo data were validated with wholemount histopathology. (4) Results: Lesions were visible in the reconstructed SWEI volume for both phantom and in vivo data, with higher shear-wave speeds inside the lesion compared with the surrounding background. The 2D shear-wave speed calculation produced more homogeneous estimates compared with a conventional 1D algorithm, which had elevated biased estimates of shear-wave speed.…”
Section: Estimation Of Mechanical Anisotropy From Arfi-induced Peak Dmentioning
confidence: 98%